Kepastian Hukum dan Hak Kreditor Konkuren Dalam Pembatalan Perjanjian Perdamaian pada Kasus PKPU (Studi Putusan : Nomor 15/Pdt.Sus-Pembatalan Perdamaian/2022/PN.Niaga/Jkt.Pst) - ⁠Ayesha Tasya Izulkha; ⁠Moody Rizqy Syailendra P (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study discusses the legal steps that can be taken by concurrent creditors related to the acquisition of a debtor company in the bankruptcy and PKPU process, with a focus on legal certainty and protection of creditor rights. The background of this study is related to the legal complexity faced by concurrent creditors when a peace agreement is canceled, as well as the acquisition of a debtor company that can affect creditor rights. The purpose of this study is to analyze the legal steps that can be taken by concurrent creditors to ensure that their rights are protected in the process. The method used is a normative approach with an analysis of laws and regulations related to bankruptcy and PKPU, as well as a study of relevant decisions regarding the cancellation of a peace agreement. The results of the study indicate that concurrent creditors have several legal steps that can be taken, such as submitting an application for cancellation of a detrimental acquisition, opposing an acquisition agreement deed that is considered invalid, and filing a lawsuit to protect their rights in the bankruptcy and PKPU process. In conclusion, concurrent creditors must be active in fighting for their rights and using appropriate legal steps in order to obtain fair debt payments.